The Effect of Statistics on Enjoyment and Perceived Credibility in Sports Media. (February 2023) - Hahn, Dustin
Evolving media landscapes toward increasingly diverse and competitive environments in both traditional and new media requires producers regularly examine the quality of their productions. One growing line of research identifies the increasing presence and significance of statistics in sports media programming. This experiment measures the effect of statistics on enjoyment and perceived credibility by sport consumers while considering level of fanship, media source, and variations in placement within Instagram posts. Results uncover evidence that validates previous observations about statistics in media while contradicting others. Specifically, findings reveal that statistics enhance enjoyment and improve perceived credibility. Observations were consistent across fanship level. However, additional findings also suggest media source and placement of statistics influences both enjoyment and credibility as well. For both dependent variables, statistics in both the Instagram caption and image yielded significantly greater enjoyment and credibility than some other conditions including posts without statistics at all. The impact of these and other findings on sports media industry and scholarship, along with limitations and directions for future research, are discussed.